Pengembangan Sistem Informasi Persewaan Alat Pesta Terintegrasi Menggunakan Payment Gatewat (Studi Kasus : CV Mita Alat Pesta) - Fitri Zakiatul Lailia; Buce Trias Hanggara; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
CV Mita is a party equipment rental company. The entire customer service process from ordering, payment, to storage of rental data archives is done manually. This causes problems such as difficulty in accessing information by customers, the risk of data loss and errors in recording, and inefficient transaction checking. Based on the description of the problem, a solution was found by building a party equipment rental information system using the Midtrans Payment Gateway. The development of this information system is based on the Waterfall Model SDLC (System Development Life Cycle) Method. This information system is used by 4 actors with 23 functional requirements and 1 non-functional requirement. All of these requirements are designed using Unified Modeling Language (UML), Physical Data Model (PDM), and User Interface by creating wireframes. UML in this study includes activity diagrams, sequence diagrams and class diagrams. Then the design results are implemented using the programming language PHP, HTML, CSS, Javascript, Laravel Framework, and MySQL database. The testing process in this study consisted of Blackbox testing, Compatibility testing, and User Acceptance Test (UAT). Blackbox testing has 17 test scenarios that get 100% accepted results. Compatibility testing using Sortsite software with the result that the system can be run on a variety of browsers without any problem of system functional loss. Then User Acceptance Testing (UAT) produces a percentage of 83.5% on the admin page and 82.4% on the customer page. Therefore, it can be concluded that the developed system can be accepted by users with the criteria of Strongly Agree.